Project Management Enhancement through Technology - Savio, Rajesh Dominic; Dewan, Bassam (Eximia, 2023)
Purpose: The main goal of this manuscript is to evaluate the impact of technology adoption and integration on project management practices, identify challenges and solutions, and explore the potential of emerging technologies for enhancing project management efficiency and effectiveness. Scope: The study takes a global approach to assess how technology impacts project management across various industries and organizations, mainly focusing on technology adoption trends in different sectors and advanced solutions. Conclusions: The manuscript details how automation and software improve project efficiency and predictability, discusses limitations, including software glitches and downtime necessitating backup systems, and identifies AI (Artificial Intelligence) as the most prominent emerging technology.